Power Generation Using Hydraulic Speed Bump - Natsheh, Mountaser; Abumarkhia, Mo’min (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2019)
Electrical energy is essentially required for society as well as all-round development of any country. The growing demand of electrical power for different activities has forced scientists and researchers to develop alternate sources of power generation from different sources of renewable energy. Nowadays the renewable energy sources have become more popular due to their sustainability, renewability and easy availability. One of the economical and environment friendly sources of electrical power generation is the utilization of kinetic energy of vehicles passing over speed bumps over the world. This project focuses on converting the everyday speed bump reciprocating movement up and down into electrical energy, capable of using the force exerted by a vehicle passing over the speed bump as a new environmental friendly system to produce energy .which utilizes the inertia of passing vehicles on the new hydraulic speed bump, which forces hydraulic fluid to flow through a special tube, and then to rotate hydraulic motor which connects directly to alternator, then produces electricity and stores it in a battery that can be used to recharge plug-in cars, streetlights, and electric charge points for portable devices. Keywords- speed bump, renewable energy, power generation تعد الطاقة الكهربائية ضرورة أساسيه لتطور المجتمعات, وتعتبر ايضا اساسا في تطور وتقدم الدول, حيث أجبر الطلب المتزايدعلى الكهرباء, واستخدامها في الانشطة المختلفة العلماء والباحثين على تطوير مصادرجديده و بديلة لتوليد الطاقة, ففي الوقت الحاضر أصبحت مصادر الطاقة المتجددة أكثر شعبية بسبب استمراريتها, وامكانيه تجديدها, وسهولة الحصول عليها . تعد عمليه استغلال الطاقه الحركيه الناتجه عن مرور المركبات على مطبات السرعه واحدة من اهم المصادرالكهربائيه الصديقة للبيئة يوجه هذا المشروع انظاره نحو تحويل الحركه التردديه اللحظيه لمطبات السرعه صعودا وهبوطا, الى طاقه كهربائيه, وذلك من خلال استغلال القوه الناتجه من مرور المركبات على هذه المطبات, حيث يعد هذا النظام احدى الانظمه الجديده المتعلقه بتوليد الطاقه المتجدده الصديقه للبيئه, والذي يستغل مرور المركبات على المطب الهيدروليكي الحديث، حيث تم تصميم المطب بطريقه تمكنه من الهبوط والصعود نتيجه لوزن المركبه, وبالتالي اجبار السائل الهيدروليكي على المرور من خلال أنبوب خاص معد مسبقا ، والذي يقوم بدوره بتدوير محرك هيدروليكي متصل مباشره مع مولد كهربائي، ثم ينتج المولد الكهربائي الكهرباء ويخزنها في بطارية, حيث يمكن استخدامها في وقت لاحق لإعادة شحن السيارات الكهربائيه ،و اناره مصابيح الشوارع ، واستخدامها ايضا كنقاط لشحن الاجهزه المحموله. الكلمات المفتاحية – مطبات السرعة , الطاقة المتجددة , توليد الطاقة
no of pages 99, ميكانيك 17/2019
Keywords: Power Generation; Hydraulic Speed Bump